EFL STUDENTS SELF-DIRECTED LEARNING IN USING YOUTUBE TO IMPROVE LISTENING SKILLS - Nerta, Priska Oktavia; Tohamba, Citra Prasiska Puspita; Faridawati, Faridawati (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This study aims to explore how EFL students use self-directed learning to improve their listening skills on YouTube utilizing the aspects of self-management, self-monitoring & motivation. The participants in this study were four (4) EFL learners majoring in English at Universitas Muhammadiyah Kendari during the academic year 2023/2024 who utilized YouTube for self-learning. The researcher employed semi-structured interviews to acquire data for this study. Using YouTube to improve listening skills, the researcher created 20 questions on students' self-directed learning. The findings highlight students' success and progression in using the YouTube platform developing self-management skills which consists of goal management, learning methods, support, and outcomes. Self-directed learning using the YouTube platform, which incorporates self-monitoring, is critical for enhancing students' learning abilities. Cognitive and metacognitive methods, such as capturing information and summarizing knowledge, help them improve their understanding and skills. In addition, this study emphasizes the importance of intrinsic and extrinsic motivation in self-directed learning via YouTube. By gaining deeper insights into students' perceptions and experiences with YouTube for language learning, this study aims to provide valuable insights for educational practitioners to develop more effective and innovative teaching strategies.